The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/geosciences9090402
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Considerations in Site Selection for Small Modular Reactors in Saskatchewan

Abstract: Saskatchewan is one of Canada’s highest emitters of greenhouse gases, largely due to the burning of lignite coal to generate electricity. The province is also the world’s second largest producer of uranium. This research was intended to establish a process for evaluating geographical considerations in site selection for small modular reactors (SMRs) in Saskatchewan. SMRs are the next generation of electrical power, producing less than 300 megawatts (MW) and featuring a basic design that offers enhanced safety,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Poudel et al (2018) suggested that when considering the feasibility of nuclear reactors, the government's fiscal capacity and power grid capacity policies also need to be considered, and the location of reactors could be determined through social surveys and analysis of existing policies. Almalki et al (2019) gave SMR siting recommendations based on geographical considerations. In this section, the different considerations of siting criteria between SMRs and NPPs are analyzed and targeted suggestions towards each factor for SMR site selection are provided.…”
Section: Suggestions On Smr Site Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poudel et al (2018) suggested that when considering the feasibility of nuclear reactors, the government's fiscal capacity and power grid capacity policies also need to be considered, and the location of reactors could be determined through social surveys and analysis of existing policies. Almalki et al (2019) gave SMR siting recommendations based on geographical considerations. In this section, the different considerations of siting criteria between SMRs and NPPs are analyzed and targeted suggestions towards each factor for SMR site selection are provided.…”
Section: Suggestions On Smr Site Selectionmentioning
confidence: 99%
“…However, SMRs can be built relatively close to populartion areas to minimize the cost of service transmission due to its lower radiation and explosion risks compared with NPPs (Lyman, 2013;Almalk et al, 2019). In terms of economic factors, when siting SMRs, costs such as the capital cost and transmission cost will also need to be evaluated (Boarin and Ricotti, 2014;Shrestha et al, 2018;Almalki et al, 2019). According to Lokhov et al (2013), compared with traditional NPPs, twenty percent of the capital cost of SMRs will be saved because of the shorter construction period.…”
Section: Suggestions On Smr Site Selectionmentioning
confidence: 99%
“…Aleksandar Rikalovic*, Ilija Cosic, Djordje Lazarevic presented "GIS Based Multi-Criteria Analysis for Industrial Site Selection" whtere they have performed GIS-MCDM on the vector and raster data in their systems to get the result in the form of vector suitability map and raster suitability map which represents the suitable areas in different colours [4]. Raid Almalki1,*, Joseph Piwowar 2 and Julia Siemer 2 presented a system where they have used analysis using MCDM on suitability and restrictive criteria to gain the results in five categories as Unsuitable, Less Suitable, Moderately Suitable, Suitable and Very Suitable represented in different colours [5]. Xuguang Bao and Lizhen Wang*has used the co-location mapping technique named as DS4.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Electricity development in Indonesia is directed at providing electricity based on non-fossil energy as a long-term goal of national energy diversification and emission control, especially through the use of nuclear and renewable energy [ 9 ]. Nuclear power plant sites require the proper formulation of structures, systems, and components to ensure their operations remain safe during normal or abnormal conditions caused by various internal and external threats [ 10 , 11 , 12 ]. According to the International Atomic Energy Agency (IAEA), potential locations can be obtained in stages, starting at the regional level, then filtering via additional characteristics and more detailed criteria [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%